Genetic diversity of Sarawak saltwater crocodile (crocodylus porosus) using PCR-RAPD - Mohd Khairulazman, Bin Sulaiman (Universiti Malaysia Sarawak, UNIMAS, 2011)
Saltwater crocodile, Crocodylus porosus is abundant in Sarawak rivers and mainly dominating the brackish water ecosystem. Lack of data on C.porosus in Sarawak especially molecular data had limit the knowledge and ability of relevant agencies to manage this potent resource in a sustainable manner. This study is designed to document RAPD profiles of C. porosus sampled from Kuching, Bau, Serian, Sibu and Miri. Methods involved were total genomic DNA extraction using modified CTAB method and Polymerase Chain Reaction (PCR) – Random Amplified Polymorphic DNA (RAPD) using three sets of primer namely Oligo 135, OPA-01 and OPA-09. RAPD profiles generated from these three primers had successfully revealed 91.67%, 67.85% and 83.33% polymorphism respectively. Genetic dissimilarities trees generated based on RAPD profiles, indicated RAPD profile did not correlate with the location of the sample obtained and the relationships between nine crocodiles in this study was not fully resolved.